2015
DOI: 10.1038/srep16911
|View full text |Cite
|
Sign up to set email alerts
|

eIF5A1/RhoGDIα pathway: a novel therapeutic target for treatment of spinal cord injury identified by a proteomics approach

Abstract: Spinal cord injury (SCI) is frequently accompanied by a degree of spontaneous functional recovery. The underlying mechanisms through which such recovery is generated remain elusive. In this study, we observed a significant spontaneous motor function recovery 14 to 28 days after spinal cord transection (SCT) in rats. Using a comparative proteomics approach, caudal to the injury, we detected difference in 20 proteins. Two of these proteins, are eukaryotic translation initiation factor 5A1 (eIF5A1) that is involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…The MEMO1-RHOA-DIAPH1 signaling pathway plays an important role in ERBB2dependent stabilization of microtubules at the cell cortex and inhibits neurite outgrowth. Interestingly, a comparative proteomic approach performed by Liu et al (2015) (15) at the caudal segment level has shown that the eukaryotic translation initiation factor 5A1 (eIF5A1) and Rho GDP dissociation inhibitor alpha (RhoGDI␣), a member of Rho GDI family, played a major role in determining the extent of spontaneous functional recovery (15). In vitro, eIF5A1 overexpression in primary neurons increased cell survival and elongated neurite length whereas eIF5A1 knockdown reversed these effects (15).…”
mentioning
confidence: 99%
“…The MEMO1-RHOA-DIAPH1 signaling pathway plays an important role in ERBB2dependent stabilization of microtubules at the cell cortex and inhibits neurite outgrowth. Interestingly, a comparative proteomic approach performed by Liu et al (2015) (15) at the caudal segment level has shown that the eukaryotic translation initiation factor 5A1 (eIF5A1) and Rho GDP dissociation inhibitor alpha (RhoGDI␣), a member of Rho GDI family, played a major role in determining the extent of spontaneous functional recovery (15). In vitro, eIF5A1 overexpression in primary neurons increased cell survival and elongated neurite length whereas eIF5A1 knockdown reversed these effects (15).…”
mentioning
confidence: 99%
“…After binding to GTP, Rho GTPase family becomes activated Rho GTP; on the contrary, after binding to GDP, Rho GTPase family becomes inactivated Rho GDP (Jaffe and Hall, 2005;Tiedje et al, 2008). RhoGDIα blocks the dissociation of GDP from Rac1 and RhoA, making them inactive, which enhances the neurite growth, differentiation and neuroplasticity (Hancock and Hall, 1993;Liu et al, 2015). It is known that decreased methylation of Rac1 and RhoA increases their binding to RhoGDIα (Cushman and Casey, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…As described previously (Liu et al, 2015;Shang et al, 2016), the protein was extracted by RIPA lysis buffer. Complete description of methods can be found in the Supplementary Methods.…”
Section: Protein Extraction and Western Blot Analysismentioning
confidence: 99%
See 2 more Smart Citations